Chemical process control education and practice. - Bequette, B.W (IEEE Control systems magazine)
Chemical process control textbooks and courses differ significantly from their electrical or mechanical control equivalents. The primary goals of this article are to i) emphasize the distinctly challenging characteristics of chemical processes, ii) present a typical process control curriculum and iii) discuss how chemical process control courses can be revised to better meet the needs of a typical BSc-level chemical engineer. In addition to a review of material covered in a standard process control course, we discuss innovative approaches in process control education, including the use of case studies, distributed control systems in laboratories, identification and control simulation packages, and studio-based approaches combining lecture, simulation, and experiments in the same room. We also provide perspectives on needed developments in process control education